2020
DOI: 10.3949/ccjm.88a.20030
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing testosterone and DHEA: The role of androgens in women

Abstract: E strogens are the principal sex hormones responsible for female reproductive maturation and sexual characteristics. However, androgens are also important for female sexual health and well-being. 1 The physiologic effects of androgens are in part due to their role as precursors for estrogen synthesis, but these hormones also have independent effects on female reproductive tissues, mood, cognition, breasts, bones, muscles, vasculature, and other systems. 1 See related editorial, page 44Here we will discuss the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Hyodeoxycholate is a bile acid derivative, and a negative correlation between blood hyodeoxycholic acid and muscle uncoupling protein 3 gene was found, suggesting a potential impact on muscle function [ 34 ]. Androsterone sulfate is one metabolite of androgens, which may also be associated with the change of lean body mass and muscle mass [ 35 ]. This study found a negative association between androsterone sulfate and ALM, which further supports the potential link between androsterone sulfate and muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…Hyodeoxycholate is a bile acid derivative, and a negative correlation between blood hyodeoxycholic acid and muscle uncoupling protein 3 gene was found, suggesting a potential impact on muscle function [ 34 ]. Androsterone sulfate is one metabolite of androgens, which may also be associated with the change of lean body mass and muscle mass [ 35 ]. This study found a negative association between androsterone sulfate and ALM, which further supports the potential link between androsterone sulfate and muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone is a sex hormone that contributes to sexual well-being in females, 24 although direct effects on cardiovascular health have also been described. 9 Although endogenous testosterone appears to have a positive effect on male cardiovascular health in a concentration-dependent fashion, 24 it is less clear what the cardiovascular implications of testosterone are in females. Studies in females with PCOS, who often have hyperandrogenism, demonstrate a relationship between increased testosterone levels and a poorer cardiovascular profile.…”
Section: Discussionmentioning
confidence: 99%
“…In males, it is mainly responsible for promoting the development and maintenance of male sexual characteristics ( 26 ) and plays a significant role in the development and maintenance of the male skeletal system ( 27 ). It is responsible for the maintenance of sexual desire in females ( 28 ). In general, low testosterone is thought to be closely related to sexual dysfunction ( 29 ).…”
Section: Discussionmentioning
confidence: 99%